Web page for visualization of climate change scenarios in Colombia (2021)
The following paper presents the continuation of the thesis of Nicolás Díaz [1], in which a web page, called Solar Atlas, capable of visualize meteorological data in Colombian territory was developed, showing different climate change scenarios. To visualize this information, a map with climate change scenarios was designed. In this map, the meteorological variables for temperature, wind speed and irradiance can be visualized for 2484 different points that describe its estimated behavior for the period 2070 to 2099 in Colombia, for two different scenarios of greenhouse gas emission, an optimistic scenario, and a pessimistic scenario. All data was displayed using heat maps and graphs showing different behaviours for the variables. This Solar Atlas improves the gap of information that exists because there are some features that were not shared by all web atlas by enclosing the missing features and showing them in an easy way to use that is also friendly to the user.